Developing new metrics to evaluate the performance of capacity planning towards sustainable construction. (10th July 2019) - Hamzeh, Farook; Al Hattab, Malak; Rizk, Lynn; El Samad, Ghali; Emdanat, Samir
Abstract: A Since construction is considered a high waste-generating industry, research and business strategies in this field are continuously expending efforts to reduce tangible material wastes and emissions. Yet, these efforts have neglected intangible resource wastes which are equally important and critical such as those produced by improper capacity planning. Capacity planning is a vital process within construction planning that aims at matching capacity (available resources) with demand (forecasted workload) to achieve planning reliability and prevent unnecessary resource waste. However, existing construction studies and practices do not emphasize capacity planning nor do they provide clear measurement frameworks for assessing its impacts on workflow and waste generation. Therefore, the purpose of this study is to highlight the importance of capacity planning by developing new metrics that help provide a holistic understanding and visualization of capacity planning performance and provide feedback for future capacity planning adjustments. The developed metrics were then empirically applied on two well managed projects in the United States. The resulting trends reveal a mismatch problem between load and capacity resulting in wasted resources due to poor allocation strategies that negatively impacted project performance. Moreover, the findings emphasize the need for dynamic evaluation and control of capacity planning performance within project teams. This research contributes novel metrics aimed towards comprehending the underlying mechanisms that shape capacity planning and aims at guiding project teams to achieve more sustainable production flows through quantitative evaluations and adjustments. Highlights: We present a quantitative method for assessing capacity planning in construction. We derive seven capacity metrics and measure them on two case study projects. The metrics complement existing ones for a complete unbiased performance evaluation. Results show problems with capacity to load matching and wasted resource allocation. Measuring performance and highlighting issues can guide improvement strategies.